2022
DOI: 10.3390/ijerph19148629
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Life Satisfaction, Stress Perception and Coping Strategies of University Students in Belarus during the COVID-19 Pandemic

Abstract: The COVID-19 restrictions in Belarus turned out to be less stringent than those of its neighboring countries. Objective: We aimed to evaluate physical activity, life satisfaction, perception of stress, choice of coping strategies and their correlations among Belarusian students. An anonymous Internet survey was conducted among 1769 students studying at the faculties of physical culture (415), pedagogical (737), and medical (617) universities. International Physical Activity Questionnaires (IPAQ) and Satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…This study investigated the factors related to psychological abnormalities in medical students in the post-epidemic era. In concert with results from Shpakou et al's survey that medical students are less satisfied with life and have a higher level of perceived stress than other majors ( 13 ), our study found that nursing and clinical students were more likely to suffer from psychological stress, anxiety and insomnia. Of note, senior and graduate medical students reported less anxiety than younger students, and no close family member or friend infected with COVID-19 reduced medical students' risk of anxiety and depression, which was consistent with published reports.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study investigated the factors related to psychological abnormalities in medical students in the post-epidemic era. In concert with results from Shpakou et al's survey that medical students are less satisfied with life and have a higher level of perceived stress than other majors ( 13 ), our study found that nursing and clinical students were more likely to suffer from psychological stress, anxiety and insomnia. Of note, senior and graduate medical students reported less anxiety than younger students, and no close family member or friend infected with COVID-19 reduced medical students' risk of anxiety and depression, which was consistent with published reports.…”
Section: Discussionsupporting
confidence: 85%
“…A Saudi Arabia survey observed nearly 20% of respondents suffering from a moderate to severe level of anxiety relative to this pandemic; western, northern, and eastern regions were reported to be the most anxious, which may be due to western and eastern regions being the initial epicenters of COVID-19 within Saudi Arabia (11). These findings are similar to those in Wuhan, China, the epicenter of COVID-19, with medical professionals experiencing a higher level of anxiety (12). These data demonstrate that differences in geographical area result in diversity in the degree of anxiety of medical students; however, the specific reasons still need to be explored in detail.…”
Section: Discussionsupporting
confidence: 75%
“…Shpakou et al [ 46 ] noted a positive correlation of PA (IPAQ) with life satisfaction (SWLS). However, our results did not confirm such a correlation.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results did not confirm such a correlation. The above-mentioned study of Shpakou et al [ 46 ] showed that the majority of students from Belarusian universities demonstrated high PA levels. A considerable proportion of the respondents used such coping strategies as active coping, planning, seeking emotional support as well as positive revaluation and development.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to a wide range of attempts to find links between physical activity and psychological and mental health across countries, races, and ages [28]. As a result, several studies have reported the adequacy of adopting physical activity as a stress management strategy during the COVID-19 pandemic [29,30]. Studies on Koreans have also reported that various health and lifestyle-related indicators deteriorated during the COVID-19 pandemic [31][32][33].…”
Section: Introductionmentioning
confidence: 99%